2017
DOI: 10.1002/app.45445
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of metal‐phosphorus hybridized nanomaterials and the action of metal centers on the flame retardancy of epoxy resin

Abstract: The action of metals on the flame retardancy of thermoplastic has aroused much interest in recent years. However, their action on thermosets is still not clear. In this work, metal-phosphorus hybridized nanomaterials with different metal centers were prepared via hydrothermal reaction between metal hydroxide/salts with phosphinic/phosphonic acids. The loading of these hybrids in epoxy (EP) resins resulted in great change on fire resistance. Thermogravimetric analysis, solid and gas phase analysis results indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…The first stage in the range of 200–550 °C is assigned to the release of NH 3 and H 2 O, along with the formation of polyphosphate. The second stage occurring above 550 °C is attributed to the degradation of polyphosphate, with the release of phosphoric acids, poly(phosphoric acids), and phosphorus oxides . The residue amount of APP at 800 °C is only 12.71%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first stage in the range of 200–550 °C is assigned to the release of NH 3 and H 2 O, along with the formation of polyphosphate. The second stage occurring above 550 °C is attributed to the degradation of polyphosphate, with the release of phosphoric acids, poly(phosphoric acids), and phosphorus oxides . The residue amount of APP at 800 °C is only 12.71%.…”
Section: Resultsmentioning
confidence: 99%
“…The second stage occurring above 550 8C is attributed to the degradation of polyphosphate, with the release of phosphoric acids, poly(phosphoric acids), and phosphorus oxides. 24 The residue amount of APP at 800 8C is only 12.71%.…”
Section: Characterization Of Emfmentioning
confidence: 99%
“…In recent years, metal-containing flame retardants have aroused much interest. Q. Yin [182] et al prepared metal-phosphorus hybrid nanomaterials by hydrothermal reaction, including aluminum phosphinate/phosphonate (APHNR/APHNSH), ferric aluminum phosphinate/phosphonate (FPHNR/FPHNSH), and zinc phosphinate/phosphonate (ZPHNR/ZPHNSH). It was found that metal hypophosphites and phosphates showed the morphology of nanorods and nanosheets.…”
Section: Metal-containing Compoundsmentioning
confidence: 99%
“…Their intrinsic flammability has been one of the main deficiencies that restrict the utilization of epoxy resins . Heretofore, the flame retardance of various additive‐ and reactive‐type flame retardants, such as halogen‐, phosphorus‐, and silicon‐based compounds, carbon‐ and clay‐based fillers, for epoxy resins has been investigated. Compared with halogenated flame retardants as well as additive‐type flame retardants, reactive‐type halogen‐free flame retardants have advantages in the protection of environment and human health, good compatibility with resins and low detriment to inherent properties of resins.…”
Section: Introductionmentioning
confidence: 99%